(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
To identify diagnostic utilities of Anti citrullinated protein (ACCP) and Rheumatoid factor (RF) are autoantibodies (Abs directly against an self-individual antigens), Analytical study. The questioner reported for 50 patients with RA were collected from Department of Rheumatology¸ AL˗Sader Teaching Hospital. Serum levels of RF & (ACCP) Abs were determinated by enzyme ˗ linked immunosorbent assay”, while the level of erythrocyte sedimentation rate (ESR) was determined by westergreen method. Distribution of RA occur in females more than males which reached (80%) & (20%) respectively according to the patients group. The patients divided according to the age into three groups (<30)¸ (30˗50) & (>50). The percent for these groups were (16%)¸ (52%) & (32%). Among the 50 patients with RA¸ CCP and ESR 49 patients (98%) tested positive for (ACCP) antibodies¸ and 22 patients (44%) tested positive for RF. and 37 patients(74% ) tested increasing levels of ESR in RA patients. The mean value of (ACCP) & ESR shows highly significance (P<0∙05), while the RF serum levels increase significantly. Demonstrate the (ACCP) antibodies assay is a useful test for diagnosing RA. However, the use of RF and (ACCP)auto- antibodies in combination further elevated the diagnostic value for RA